"It's Like Giving Birth to This Girl Again": Social Repair and Motherhood After Conflict-Related Sexual Violence. (20th October 2021) - Oliveira, Camile; Baines, Erin
Abstract: In the strain of remaking the social world after a violent conflict, women who conceive children as the result of sexual violence must often raise them amongst resentful victim communities. Abducted and forced into marriage by the Lord's Resistance Army in northern Uganda, Acholi women are perceived to have returned with the children of the enemy and are subsequently told they do not belong. Based on ten years of collaborative research with war-affected mothers in northern Uganda, we consider the ways women repair webs of kin relations to secure a future no longer dictated by the circumstances of their children's birth.